Registration and Licensure of Nutrition Professionals in Florida - Linda B. Bobroff (EDIS)
This document provides information about dietetic registration (a national credential), and licensure (a state-specific credential). Forty-six states have their own form of licensure or credentialing for nutrition professionals. In Florida, there are three credentials that allow people to legally practice as a nutrition or dietetics professional: Registered Dietitian (RD), Licensed Dietitian/Nutritionist (LD/N), and Licensed Nutrition Counselor (LNC). Specific areas of practice, such as private consulting, public health, and long-term care, have different requirements. This document is FCS 8765, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2004.